Evaluation of the rate of Chlorella vulgaris biofilm on polyvinyl chloride microplastics in aqueous solutions - Afsaneh Esmaeili Nasrabadi; Ziaeddin Bonyadi (Results in Engineering)
Microplastics (MPs) are emerging pollutants that significantly impact human health and the environment. This study aimed to investigate the formation rate of Chlorella vulgaris biofilm on polyvinyl chloride (PVC) microplastics in aqueous solutions. The findings revealed that biofilm growth reached 28 mg/g, 54 mg/g, and 140 mg/g on the third, sixth, and ninth days, respectively. Furthermore, the highest chlorophyll concentrations for Chl a and Chl b were found to be 11.43 μg/g and 10.18 μg/g, respectively. The maximum extracellular polymeric substances (EPS) concentration was recorded at 12.25 mg/g on the same day. The results also revealed that the formation of biofilm on PVC led to a decrease in the zeta potential (ZP) of PVC from -25.6 mV to -34.9 mV. Dynamic Light Scattering (DLS) analysis revealed an increase in particle size from 353.5 nm to 995 nm, which can be attributed to the aggregation of C. vulgaris cells and biofilm formation on PVC surfaces. This study demonstrated that exposure to PVC significantly affects algal growth, pigment concentration, EPS production, photosynthetic structures, and aquatic biological processes. These findings highlight the potential ecological threats that PVC poses to aquatic ecosystems.